Non-Linear Pushover Analysis of Tall Buildings with Post-Tensioned Slabs and Rigid Core Designed Under Peruvian Codes - Cruces, Cristhian (2022)
Currently at Peru tall building over 30stories began to be built. However, Peru structural design codes are based on medium and low-rise buildings. As well, posttension slab is used to these high rise buildings. The objective of this research was to evaluate the behavior of 6 high-rise buildings through nonlinear Pushover analysis. These buildings include rectangular and square floor plans of 40, 36 and 32 floors, and were designed considering the Peruvian regulations E 0.20 'Loads', E 0.30 'Earthquake Resistant Design' and E 0.60 'Reinforced Concrete'. Rigid core systems were used, varying the compressive strength of the concrete. Also 35 cm thick post-tensioned slabs were used as part lateral structural resistant system, which behavior presented high punching shear forces due earthquake loads. The results of the nonlinear pushover analysis show that the capacity curves are fragile because the hinges of the walls fail in shear instead of in bending moment-compression. On the other hand, it was also found that buildings with 32 and 26 levels with a rectangular floor plan are unable to meet the displacement demand.